Contradictions finance, greed, and labor unequally paid - Zarembka, Paul (Emerald, 2013)
This volume analyzes two decisive factors that have become embedded in the world spread of capitalism, a shift toward dominance of the financial sector, now entailing massive greed and calling into question whether the rules of capitalism have been broken, and of global wage differentials so deep that recognition of a labor aristocracy cannot be avoided. These chapters are supplemented by two additional showing that gold still regulates the dollars value, and that unpaid reproductive labor of women adversely affects labor productivity. Analysis of finance engenders discussion of its place in value theory, posed around the rate of profit, and is more complex than often presented. Furthermore, the varying rates of profit at the firm level, not just for financials, are distributed in a manner exhibiting more frequent extreme cases than a Bell-curve would suggest. Implications for incorporation of randomization into political economy are drawn. The final chapters provide evidence that Marx was more correct than Kalecki and Minsky when arguing the lead of profits for investment, and that product innovations can mitigate problems of over-production resulting from process innovations.
Keywords: Marxian economics.; elektronické knihy; electronic books